2020
DOI: 10.1021/acssuschemeng.0c06712
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde from Lignin Acidolysis Might Be Useful for In-Line Control of Industrial Biomass Processing

Abstract: Wood processing typically involves heating that generates lignin-borne formaldehyde, a well-known aspect of lignin acidolysis that played an important role in early efforts to elucidate lignin structure. Previously, we found that lignin-borne formaldehyde accounts for a small percentage of lignin acidolysis. This is explained by two competing lignin acidolysis pathways, C2 cleavage producing formaldehyde, and C3 cleavage (no formaldehyde). Here, the topic was studied with industrial-scale thermomechanical refi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…34−36 According to Martin-Sampedro et al, the second peak temperature indicates the state of in situ lignin cross-linking, where higher peak temperatures signify more lignin cross-linking, and vice versa. 37,38 Table 4 partially supports this claim where it shows that, relative to the unheated control, all heat treatments significantly increased the second peak temperature. It is recalled that DSC and SEC indicated significantly different cross-linking levels in MWL from pinewood heated with HCl or H 2 SO 4 , being the greatest in the latter.…”
Section: ■ Results and Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…34−36 According to Martin-Sampedro et al, the second peak temperature indicates the state of in situ lignin cross-linking, where higher peak temperatures signify more lignin cross-linking, and vice versa. 37,38 Table 4 partially supports this claim where it shows that, relative to the unheated control, all heat treatments significantly increased the second peak temperature. It is recalled that DSC and SEC indicated significantly different cross-linking levels in MWL from pinewood heated with HCl or H 2 SO 4 , being the greatest in the latter.…”
Section: ■ Results and Discussionmentioning
confidence: 56%
“…Above the presumed dehydration near 100 °C, oxidative dTGA revealed two peaks, one near 350 °C (first peak) and another near 500 °C (second peak). Some have claimed that the first and second peaks, respectively, reflect the separate degradation of polysaccharides and lignin. , However, it has been shown that this interpretation is too simplistic, particularly for the second peak which reflects multiple events. According to Martin-Sampedro et al, the second peak temperature indicates the state of in situ lignin cross-linking, where higher peak temperatures signify more lignin cross-linking, and vice versa. , Table partially supports this claim where it shows that, relative to the unheated control, all heat treatments significantly increased the second peak temperature. It is recalled that DSC and SEC indicated significantly different cross-linking levels in MWL from pinewood heated with HCl or H 2 SO 4 , being the greatest in the latter.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…7 Third, formaldehyde can also be obtained from the acid hydrolysis of lignin. 8 In the previous work by our group, 9 it was found that jet fuel range polycycloalkanes could be obtained from the hydrodeoxygenation of bisphenols that may be produced with phenol, a model compound that can be obtained from the hydrogenolysis of lignin. To the best of our knowledge, there is no report about the synthesis of polycycloalkane from lignin-derived phenols that were connected with other functional groups (such as -OCH 3 group and alkyl group).…”
Section: Introductionmentioning
confidence: 99%